2017
DOI: 10.6001/zemesukiomokslai.v24i3.3555
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting goat milk fat yield

Abstract: The objective of the paper was to investigate the main factors determining the yield of fat in goat milk in the dairy goat population of Lithuania. The research was carried out on a total of 1,079 dairy goats (4 breeds: Czech White Shorthaired (n = 610), Saanen (n = 364), Lithuanian native (n = 94) and Anglo-Nubian (11)) in 7 dairy farms. The average milk yield during lactation was 797.42 (±53.3) kg. The average milk fat content was 4.14% (±0.4). The research of the goat milk fat content demonstrated that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…Despite the lack of seasonal differences in the composition of goat whey of the present study, it is reported that breed, animal feed, farming systems (particularly the extensive system), lactation and milking usually affect the amount and quality of milk used for cheese production, which are related to the seasonal changes that can occur in the composition of cheese whey (Ferro, Tedeschi & Atzori, 2017;Šlyžius, Šlyžienė & Lindžiūtė, 2017). Therefore, it is possible to assume that the animals used in milk production (Saanen goats), that produced the resulting whey for this study, were most likely receiving the same amount of nutrients during the summer and winter months.…”
Section: Discussionmentioning
confidence: 63%
“…Despite the lack of seasonal differences in the composition of goat whey of the present study, it is reported that breed, animal feed, farming systems (particularly the extensive system), lactation and milking usually affect the amount and quality of milk used for cheese production, which are related to the seasonal changes that can occur in the composition of cheese whey (Ferro, Tedeschi & Atzori, 2017;Šlyžius, Šlyžienė & Lindžiūtė, 2017). Therefore, it is possible to assume that the animals used in milk production (Saanen goats), that produced the resulting whey for this study, were most likely receiving the same amount of nutrients during the summer and winter months.…”
Section: Discussionmentioning
confidence: 63%
“…Goats are among the earliest domesticated animals that have been raised by humans for at least 10 000 years 22 . Due to their adaptability to different environmental and climatic conditions, they are dispersed all over the world (except Antarctica) and are considered beneficial animals to humans, providing milk, meat and wool 23,24 . Goat eyes are frequently used in ophthalmic research, 25,26 because of anatomic similarities to the human globe and due to their availability 26 .…”
Section: Introductionmentioning
confidence: 99%
“…22 Due to their adaptability to different environmental and climatic conditions, they are dispersed all over the world (except Antarctica) and are considered beneficial animals to humans, providing milk, meat and wool. 23,24 Goat eyes are frequently used in ophthalmic research, 25,26 because of anatomic similarities to the human globe and due to their availability. 26 Goat eyes also serve as an eye model for training of new surgeons practicing phacoemulsification.…”
mentioning
confidence: 99%